The Development E-Ting Application To Improve The English Writing Skill - Yuyun Bahtiar; Nur Herlina; Iin Baroroh Ma’arif; Luluk Choirun Nisa’ Nur (SCHOOLAR: Social and Literature Study in Education, 2024)
In English there are four skills namely reading, writing, listening and speaking. Speaking can be done spontaneously very different from writing which must pay attention to grammar and others, the purpose of this study is to design an android application that can help students develop their writing skills. This study uses the research and development method with the ADDIE model to design an application called "E-Ting" English writing. This media has been validated by media validation experts and also material validation experts. Data collection instruments carried out from the results of interviews only, the results of media validation obtained a score of 96 which was categorized as very good, for material validation obtained a score of 81 with a very good category and the results of the application of the media obtained a score of 78 with a good category. Based on the above results, the researcher concludes that the "E-Ting" English Writing application is feasible to use at SMK Kreatif Hasbullah Bahrul 'Ulum Jombang.